2022
DOI: 10.3390/jpm12050846
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Management of Patients with Chronic Rhinosinusitis with Nasal Polyps in Clinical Practice: A Multidisciplinary Consensus Statement

Abstract: Chronic rhinosinusitis (CRS) is a sino-nasal chronic inflammatory disease, occurring in 5–15% of the general population. CRS with nasal polyps (CRSwNP) is present in up to 30% of the CRS population. One-third of CRSwNP patients suffer from disease that is uncontrolled by current standards of care. Biologics are an emerging treatment option for patients with severe uncontrolled CRSwNP, but their positioning in the treatment algorithm is under discussion. Effective endotyping of CRSwNP patients who could benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 82 publications
1
20
0
Order By: Relevance
“…Up to 30% of patients with CRS have nasal polyps. The symptoms of CRSwNP are uncontrolled by current standards of care in one-third of patients, especially in cases associated with high levels of eosinophils such as aspirin-exacerbated respiratory disease (31). Sinonasal surgeries and/or corticosteroids are the most common treatments for CRSwNP.…”
Section: Considerations For Systemic Eosinophilic Diseases: Egpa and Hesmentioning
confidence: 99%
“…Up to 30% of patients with CRS have nasal polyps. The symptoms of CRSwNP are uncontrolled by current standards of care in one-third of patients, especially in cases associated with high levels of eosinophils such as aspirin-exacerbated respiratory disease (31). Sinonasal surgeries and/or corticosteroids are the most common treatments for CRSwNP.…”
Section: Considerations For Systemic Eosinophilic Diseases: Egpa and Hesmentioning
confidence: 99%
“…The evaluation of CRSwNP is usually performed by collecting information via medical history and scoring tools to determine disease severity and level of control 4 . Notably, endo-phenotyping is particularly relevant prior to the initiation of biologics 5 . This will be even more important in the future, given that, in addition to the anti-IL-4/13 dupilumab, the anti-IgE omalizumab is now available for prescription and that Italian Medicines Agency (AIFA) has approved the anti-IL-5 agent mepolizumab for CRSwNP.…”
Section: Introductionmentioning
confidence: 99%
“…However, the real-world utilisation of different diagnostics and their impact on the management of CRSwNP remain the object of discussion. Another aspect that should be investigated is the role of multidisciplinary referrals for this condition 5 .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In recent years, monoclonal antibodies (mAbs) that target IL-5 or IL-4/IL-13 signaling pathways have been introduced as add-on treatment. 10 High tissue infiltration of eosinophils is commonly regarded as a hallmark of difficult-to-treat CRSwNP. However, studies have shown that pharmacological depletion of eosinophils in peripheral blood or NP tissue may not improve symptoms or affect disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…CRSwNP is predominantly a type 2 T‐helper cell (Th2)‐driven inflammation characterized by interleukin (IL)‐4, IL‐5, IL‐13, as well as infiltrating eosinophils, mast cells, and type 2 innate lymphoid cells (ILC2s) 7–9 . In recent years, monoclonal antibodies (mAbs) that target IL‐5 or IL‐4/IL‐13 signaling pathways have been introduced as add‐on treatment 10 . High tissue infiltration of eosinophils is commonly regarded as a hallmark of difficult‐to‐treat CRSwNP.…”
Section: Introductionmentioning
confidence: 99%